2015
DOI: 10.1186/s12904-015-0039-6
|View full text |Cite
|
Sign up to set email alerts
|

How do junior doctors in the UK learn to provide end of life care: a qualitative evaluation of postgraduate education

Abstract: BackgroundThe fundamental importance of good end of life care has been well documented however recent national publications have high-lighted inadequacies in training in this area. For many patients dying in the UK today care is provided in hospital and the number of inpatient deaths is forecast to climb significantly in future. The demands of providing medical care for these patients by junior doctors will continue to rise. However, there is currently only limited research on training for doctors in this sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 20 publications
0
37
0
Order By: Relevance
“…Despite recommendations that a senior clinician is involved in recognising dying, the EOLCA identified that for a quarter of patients (24%) this did not happen . The data highlight the importance of senior support for FYs in this regard, which is echoed elsewhere for juniors further along in their training . Where senior clinicians remain actively involved in the care of the dying, better care is provided by the whole team, who are supported in this.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Despite recommendations that a senior clinician is involved in recognising dying, the EOLCA identified that for a quarter of patients (24%) this did not happen . The data highlight the importance of senior support for FYs in this regard, which is echoed elsewhere for juniors further along in their training . Where senior clinicians remain actively involved in the care of the dying, better care is provided by the whole team, who are supported in this.…”
Section: Discussionmentioning
confidence: 80%
“…Models exist but are variably implemented . The palliative care team was identified as an important source of support, which is reinforced elsewhere . Clinical, practical and emotional support for all doctors caring for dying patients has been identified by the British Medical Association as important .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7,8 They have described 'being left' to cope, fearful that their lack of experience could make things worse for patients. 9 Palliative care is often learnt on the job, with little formal teaching. 10 F1s can find communication about end-of-life decisions and recognition of the dying phase challenging and can also lack knowledge of cancer care and symptoms.…”
Section: Introductionmentioning
confidence: 99%